Digital platforms and European Union law – challenges from a perspective of multilevel constitutionalism - Enes, Graça (2019)
Present economy and society are under a “digital revolution”. Digital platforms connect service and product suppliers to recipients all around the world creating new businesses and changing business models in place. Old-fashioned informal gig-economy and sharing practices by using the new technology seem to change consumption and production patterns to more efficient and sustainable ones… or maybe not. This “new economy” also poses several challenges to law questioning the adequacy of concepts and regulations in force. Disputes with authorities and incumbent industries end up in violence or in courts, including the European Court of Justice. We intend to give an overview of those challenges, especially in light of European Union law and following a multilevel constitutionalist approach, which we believe is best suited to respond to the regulatory challenges of this “new economy”.